Algorithms for multiaxial cycle counting method and fatigue life prediction based on the weight function critical plane under random loading. (September 2019) - Wang, Xiao-Wei; Shang, De-Guang; Sun, Yu-Juan; Liu, Xiao-Dong
Based on the critical plane determined by the weight function method, two algorithms for multiaxial cycle counting method are proposed by modifying the rainflow and range cycle counting methods. The proposed two algorithms can be applied to multiaxial random loading, and be suitable to any critical plane-based fatigue life prediction models, since the counted cycles or reversals are represented by the start time and end time. The proposed two algorithms are used to predict multiaxial fatigue life by the experimental data of 7075-T651 aluminum alloy, En15R steel and 7050-T7451 aluminum alloy conducted under multiaxial random loading in both high-cycle and low-cycle fatigue region. The life prediction results are in good agreement with the experimental data.